RASIONALITAS EKONOMI KEWAJIBAN ZAKAT - Saqina Putri, Zharfa Athirah; Indrasari, Widya; Fawwaz, Muhammad Daffa (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2024)
Zakat as one of the pillars of Islam explains the special obligation to issue a portion of individual wealth for social good. Much literature examines zakat from various aspects, both from the legal aspect (fiqh), management, its potential and role in poverty alleviation. Indonesia, as a country with the largest Muslim population in the world, certainly has the potential to become a surplus country in the field of zakat, of course, if it is managed optimally, professionally and accountability. It can be proven that in recent decades, amil zakat bodies and institutions (BAZ/LAZ) have been formed. Then there is the community as the most important element in the management of zakat, because it is the community who is the giver and at the same time the beneficiary of zakat management. Apart from that, in the context of economic rationality, there is also a professional zakat that can help narrow the income gap and expand opportunities for those who are less fortunate. As well as in the Islamic consumption pattern, consumption is more influenced by needs than wants and takes into account utility which is oriented towards the hereafter. Zakat sebagai salah satu pilar Islam yang menjelaskan tentang kewajiban khusus dalam mengeluarkan sebagian kekayaan individu untuk kebaikan sosial. Banyak literatur yang mengkaji zakat dari berbagai aspek, baik dari aspek hukum (fiqh), manajemen, potensi maupun peranannya dalam pengentasan kemiskinan. Indonesia sebagai negeri yang berpenduduk masyarakat Muslim terbesar di dunia, tentunya memiliki potensi menjadi negeri yang surplus di bidang zakat tentunya jika hal tersebut dikelola secara optimal, professional dan akuntabel. Dapat dibuktikan dari beberapa dekade belakangan ini telah terbentuk badan dan lembaga amil zakat (BAZ/LAZ). Kemudian terdapat masyarakat sebagai elemen terpenting dalam pengelolaan zakat, karena masyarakat lah yang menjadi pihak pemberi dan sekaligus juga penerima manfaat dari pengelolaan zakat. Selain itu dalam konteks rasionalitas ekonomi, terdapat juga zakat profesi yang mampu membantu mempersempit kesenjangan pendapatan dan memperluas peluang bagi mereka yang kurang beruntung. Serta dalam pola konsumsi Islam, konsumsi lebih banyak dipengaruhi oleh kebutuhan (needs) daripada keinginan (wants) dan lebih memperhitungkan utilitas yang berorientasi akhirat.